The Implementation of the Empowerment Model of Women Farmer Groups “Minangkabau” in Managing Sustainable Food Security - Rinda Yanti; Hasan Ibrahim (Universitas Airlangga, 2021)
This research aims to explore the empowerment model of Minangkabau woman farmer groups was implemented to manage sustainable food security.